Some hints on individual lending and different factors affecting the credit activity risks - CERNENCO, Luminiţa; LAZARENCO, Marilena (Annals of Spiru Haret University. Economic Series, 2016)
The bank crediting responds to some economical necesities with objective feature ( the stimulation of the production , the stimulation of the competition , the correlation of the needs of the capital with the posibilities of the formation of this ) . We can say that the humanity lives through credit , because the credit expands through the relationships with the external partners , in the most complexe domains of activity . The increase of the credit portofolio was characteristic of the activity developed of all sections of customers , both the credits given to individual or to companies . This evolution was determined of actions sustained by the selling and promotion of the new credit products .